Anaerobic digestion of food waste with chicken manure for hydrogen and methane production - Tuan Yusof, Tengku Roslina (2019)
Recently, environmental concerns associated with animal manure and food waste management generated from the feedlot farming and restaurants in Malaysia needs to be carefully addressed. Biogas production from anaerobic digestion of chicken manure and food waste is regarded as an alternative, due to the simultaneous benefits of environmental pollution control and meeting the national energy demands. Although anaerobic digestion is a common process for treatment of chicken manure and food waste. However, mono-digestion of food waste often leads to digester instability due to the rapid conversion of the easily digestible food waste to volatile fatty acids (VFAs) resulting in a drastic pH drop if no sufficient buffering capacity is present. Therefore the approaches include co-digestion with chicken manure could be beneficial to enhance balance of nutrients, and synergistic effect of microorganisms. The inhibitions effects of biogas production can be overcome by optimizing the physical parameters during hydrogen and methane gas production. The objectives of this study were to establish the optimum operating parameters for hydrogen and methane production from co-digestion of food waste with dry and fresh chicken manure mixed at different ratio. The batch fermentation was conducted using 150 mL serum bottles incubated in anaerobic condition at mesophilic temperature. Food waste was taken from cafeterias with composition ratios 2:1:1 carbohydrate, protein and fiber were prepared. Chicken manure collected from the chicken farm was diluted with water at ratio 1:1. Hydrogen and methane production were performed at different ratio of chicken manure and food waste (0:100, 10:90, 20:80, 30:70, 40:60, 50:50 and 100:0) at initial pH 7. The selected ratio from serum bottle was tested in 500 mL anaerobic digesters with working volume 400 mL at temperature at 35°C. The comparison between dry chicken manure and fresh chicken manure with food waste shows that the highest biogas (972 mL) produced was mixture of fresh chicken manure with food waste in batch system at ratio of 30:70. The highest hydrogen and methane yields obtained were 133.3 and 26.6 mL/gVS, respectively. The community structures of microorganism and their metabolic capability play important roles in hydrogen and methane fermentation processes. The 16S metagenomics analysis was conducted. Tagged 16S rRNA gene pyrosequencing analysis for selected ratio 30:70 of CM:FW showed that the seed culture comprised largely from phyla Proteobacteria, Bacteroidetes, and Firmicutes. During mesophilic hydrogen fermentation, phylum of Firmicutes (40%) was dominant at day 1, while phylum of Firmicutes (15%) was dominated at day 13. Clostridium sp. was the main species detected in the acidogenic phase, while Methanosaeta consilii and Methanosaeta hungatei were detected during methanogenic phase. In this study, the anaerobic digestion was scaled up using 5 L stirred tank bioreactor and was used to improve the biogas production from co-digestion of chicken manure with food waste at ratio 30:70 in batch operation. The experiment was carried out at different temperatures (30, 35, 45 and 55°C). The initial pH was set up at 5.0 and 7.0 for hydrogen and methane gas production, respectively. Gompertz and logistic model were used to evaluate kinetics of hydrogen and methane gas production. The result showed that the reactor with operating temperature of 45oC achieved maximum cumulative hydrogen and methane gas production. The maximum hydrogen and methane yield were 112.4 and 130.87 mL/gVS, respectively. After that, the optimum temperature of 45oC was selected for semi continuous modes using 5L bioreactor. The effect of co-digestion chicken manure with food waste on hydrogen and methane production was investigated at different organic loading rate (OLR) and hydraulic retention time (HRT). The digestion was conducted at varied HRT of 10 and 15 d, and OLR of 0.8 and 1.24 (g VS)/L.d for methane production while for hydrogen production at HRT (18 h, 12 h and 4 h) at OLR (17.7, 34.8 and 50.4) gVS/L.d. The pH was controlled for hydrogen and methane gas production at 5.0-5.5 and 6.0-7.0, respectively. The results indicated that stable hydrogen and methane gas production were achieved from co-digestion of chicken manure and food waste. The highest hydrogen and methane yields were 127.4 and 388.4 mL/g VS at OLR 34.8 and 0.8 g VS/L.d, respectively.